Socio-demographic and Disease Profile of the Patients Attending the Surgical Outpatient Department at a Tertiary Care Hospital (Jalalabad Medical Journal, 2026)
Surgical interventions are crucial in treating various medical conditions. As cancers, cardiovascular diseases, and injuries rise, surgical impacts on public health grow. Effective surgeries rely on advanced instruments for tissue manipulation. Hospitals integrate outpatient and inpatient services, with patients often treated as outpatients before inpatient admission and follow-up. Hospital outdoor spaces can positively affect health outcomes. Surgical outpatient evaluations involve multidisciplinary preoperative assessments to determine fitness and optimise resource use. Tertiary care centres face challenges in managing high patient volumes and diverse conditions, necessitating continual adaptation and enhancement of practices. This study aimed to analyse surgical outpatient disease profile at a tertiary care hospital to enhance patient care and resource management. This cross-sectional observational study was conducted at Jalalabad Ragib-Rabeya Medical College Hospital in Sylhet, Bangladesh, enrolling 15,047 patients based on records from 01.01.2022 to 31.12.2023. Patients were evaluated and treated in the outpatient department of surgery, with those requiring surgery, mild cases given medication and advice, and others referred for further care. Inclusion criteria encompassed all ages and sexes with mild to moderate symptoms, while emergency cases and patients with gynaecological conditions or pregnancy were excluded. The largest age group was 25-49 years (48.5%) followed by 15-24 years (27.2%) and those over 50 (24.1%). Females comprised 68.8% of patients, with males at 31.2%. The most prevalent disease categories were anorectal diseases (14.9%), urology (12.6%) and breast diseases (10.6%). Additional common conditions included non-specific abdominal pain, gallbladder diseases, minor trauma, and post-operative follow-up cases. Most patients (54.8%) were managed with non-surgical advice/investigations, while 23.7% required admission. Surgical outpatient evaluations at a tertiary care hospital are crucial for managing diverse medical conditions, with anorectal and urological diseases being the most common. Over half of the patients required only medical advice or investigations, highlighting the efficiency of outpatient services in comprehensive patient management and resource utilisation in tertiary care settings.Jalalabad Med J 2025; 22 (2): 67-71